FOREIGN EXPERIENCE OF PREPARING STUDENTS FOR INTERNATIONAL ASSESSMENT PROGRAMS IN THE EDUCATIONAL SYSTEM - Kunduz , Alimova (PT. Antis International Publisher, 2024)
: In this article, we will get acquainted with the STEAM educational technology, which the most developed top countries of the world are actually testing in the development of their educational systems. And we will consider the analysis of the results of international evaluation programs created to measure the effectiveness of education in Uzbekistan.